Preclinical Evidence of Paeoniflorin Effectiveness for the Management of Cerebral Ischemia/Reperfusion Injury: A Systematic Review and Meta-Analysis - Wang, Anzhu; Zhao, Wei; Yan, Kaituo; Huang, Pingping; Zhang, Hongwei; Ma, Xiaochang (Frontiers in Pharmacology, 2022)
Background: Vessel recanalization is the main treatment for ischemic stroke; however, not all patients benefit from it. This lack of treatment benefit is related to the accompanying ischemia-reperfusion (I/R) injury. Therefore, neuroprotective therapy for I/R Injury needs to be further studied. Paeonia lactiflora Pall. is a commonly used for ischemic stroke management in traditional Chinese medicine; its main active ingredient is paeoniflorin (PF). Purpose: We aimed to determine the PF’s effects and the underlying mechanisms in instances of cerebral I/R injury. Study Design: We searched seven databases from their inception to July 2021. Methods: SYRCLE's risk of bias tool was used to assess methodological quality, and STATA 12.0 software was used for meta-analysis. Results: Thirteen studies including 282 animals overall were selected. The meta-analyses showed compared to control treatment, PF significantly reduced neurological severity scores, cerebral infarction size, and brain water content (P = 0.000). In the PF treatment groups, the apoptosis cells and levels of inflammatory factors (IL-1β, TNF-α, and IL-6) decreased compared to those in the control groups (P = 0.000). Conclusions: Our results suggest that PF is a promising therapeutic for cerebral I/R injury management. However, to evaluate the effects and safety of PF in a more accurate manner, additional preclinical studies are necessary.